2019
DOI: 10.1172/jci127613
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiological androgens suppress prostate cancer growth through androgen receptor–mediated DNA damage

Abstract: Prostate cancer (PC) initially depends on androgen receptor (AR) signaling for survival and growth. Therapeutics designed to suppress AR activity serve as the primary intervention for advanced disease. However, supraphysiological androgen (SPA) concentrations can produce paradoxical responses leading to PC growth inhibition. We sought to discern the mechanisms by which SPA inhibits PC and to determine if molecular context associates with antitumor activity. SPA produced an ARmediated, dose-dependent induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 62 publications
2
75
1
Order By: Relevance
“…Potentially, tumors with DNA repair alterations are more sensitive to HDT. In a recent study, supraphysiologic androgen was shown to repress genes in DNA repair and delay restoration of damaged DNA and an enhanced effect in patients with DNA damage repair genes was observed [22]. Additionally, a case report on a germline BRCA2 and ATM positive patient treated with BAT achieved an undetectable PSA after 2 cycles, complete radiographic response after 6 cycles, and unmeasurable disease after 20 cycles [23].…”
Section: Discussionmentioning
confidence: 98%
“…Potentially, tumors with DNA repair alterations are more sensitive to HDT. In a recent study, supraphysiologic androgen was shown to repress genes in DNA repair and delay restoration of damaged DNA and an enhanced effect in patients with DNA damage repair genes was observed [22]. Additionally, a case report on a germline BRCA2 and ATM positive patient treated with BAT achieved an undetectable PSA after 2 cycles, complete radiographic response after 6 cycles, and unmeasurable disease after 20 cycles [23].…”
Section: Discussionmentioning
confidence: 98%
“…This is in contrast with previous reports on prostate cancer cells, in which AR inhibition, while synthetically lethal with other treatments ( Karanika et al, 2017 ; Li et al, 2017 ), does not appear to be sufficient to induce DNA damage and downstream events by itself. In fact, a number of reports indicate that DNA damage can be induced in prostate cancer cells by overstimulation of AR activity ( Chatterjee et al, 2019 ; Lin et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human prostate cancer, supraphysiological androgen levels induce senescence [70]. Recent findings by Chatterjee et al [71] confirmed that elevated androgen levels play a protective role. The present study is in agreement with the findings of Wang et al [72], demonstrating potential implications of senescence along with aging in declining male fertility.…”
Section: Discussionmentioning
confidence: 94%